Implementation of the Duties and Authorities of the Community Health Center in Managing Medical Waste as a Form of Environmental Health Protection (Case Study at the Wonosalam 2 Health Center, Demak) - Raudhotul Jannah; Eko Nurmardiansyah; Hadi Sulistyanto (Soepra: Jurnal Hukum Kesehatan, 2023)
Health is one of the human rights, the fulfillment of which is the responsibility of the government in every country, Puskesmas is the agency that organizes government affairs in the health sector in the sub-district. The author chose the Wonosalam 2 Demak Health Center as the object of this research.